2016
DOI: 10.1086/688401
|View full text |Cite
|
Sign up to set email alerts
|

Ant Mutualism Increases Long-Term Growth and Survival of a Common Amazonian Tree

Abstract: How ecological context shapes mutualistic relationships remains poorly understood. We combined long-term tree census data with ant censuses in a permanent 25-ha Amazonian forest dynamics plot to evaluate the effect of the mutualistic ant Myrmelachista schumanni (Formicinae) on the growth and survival of the common Amazonian tree Duroia hirsuta (Rubiaceae), considering its interactions with tree growth, population structure, and habitat. We found that the mutualist ant more than doubled tree relative growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A good example is the mutualism between the common Amazonian tree Duroia hirsuta and Myrmelachista schumanni ants, which kill all vegetation other than their host plants in so-called devil's gardens. An 18 year study revealed that ants significantly increase the growth and survival of this common tree [68], thus negatively affecting species coexistence. This acts as a 'destabilizing' mechanism by making the mutualist competitively superior.…”
Section: Other Mechanisms By Which Mutualisms Restrict Species Coexis...mentioning
confidence: 99%
“…A good example is the mutualism between the common Amazonian tree Duroia hirsuta and Myrmelachista schumanni ants, which kill all vegetation other than their host plants in so-called devil's gardens. An 18 year study revealed that ants significantly increase the growth and survival of this common tree [68], thus negatively affecting species coexistence. This acts as a 'destabilizing' mechanism by making the mutualist competitively superior.…”
Section: Other Mechanisms By Which Mutualisms Restrict Species Coexis...mentioning
confidence: 99%
“…Despite the potential importance of EFN for ants, the majority of ant-plant systems are studied unilaterally from the plant's perspective (Bronstein, 1994;Lanan & Bronstein, 2013). There is strong evidence for ant partners reducing herbivory (Rudgers et al, 2010) and herbivore diversity (Pringle & Gordon, 2013), and enhancing nutrient availability (Mayer et al, 2014;Wagner & Fleur Nicklen, 2010), growth, and survival (Báez et al, 2016), all of which benefit the plant partners. Much less is known about the consequences of ant-plant mutualism from the ant's perspective (but see Byk &Del-Claro, 2011 andBronstein, 2013).…”
Section: Introductionmentioning
confidence: 99%